Stellera chamaejasme L. extracts in the treatment of glioblastoma cell lines: Biological verification based on a network pharmacology approach - Wang, Kaiyue; Wang, Zengyong; Wang, Zhiqiang; Xie, Xiaoli; Zang, Lanlan; Wang, Lijuan; Che, Fengyuan (Frontiers in Oncology, 2022)
Background: Stellera chamaejasme L (RXLD) has been demonstrated with good clinical effects and medicinal value in the treatment of cancer in vivo and in vitro. Specifically, RXLD can eliminate aggregation accumulation, which is depicted as a vital characteristic feature of intracranial tumors. The potential pharmacological mechanisms of anti-glioblastoma (GBM) have not been adequately identified. Methods: The 3D structures of the chemical ingredients in RXLD were imported into the PharmMapper database to construct the pharmacophore models. The gene targets of GBM were obtained from databases. The pharmacophore-targets network and the protein-protein interactions (PPI) were constructed using the String database and were visualized by using Cytoscape. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway (KEGG) enrichment analyses were conducted using Bioconductor software. Cytoscape visualized the relationship of pathways and candidate genes to screen for key target genes. Software packages PyMOL, AutoDock, and Vina acquired the molecular docking results. In vitro experiments were undertaken to characterize RXLD extracts’ effects on A172 cell line proliferation, viability, apoptosis, cell cycle, cell wound healing, cell migration, reactive oxygen species generation, and mitochondrial membrane potential. The expression of core genes in the related pathways was detected by Western blotting. Results: We identified 216 potential targets associated with GBM. The core components in RXLD were neochamaejasmin A, wikstrol A, isochamaejasmin, chamaejasmine, and subtoxin A. The undertaken GO enrichment analysis revealed that oxidative stress, cell proliferation, cell cycle, cell invasion, and cell migration were involved in the biological processes. The KEGG enrichment analysis revealed that the crucial pathway was MAPK pathway, while HRAS, PRKCB, MAPK9, CCND1, and TP53 were distributed in core locations. A total of seven RXLD pharmacophores demonstrated strong spontaneous docking activities with MAPK9. In vitro assays indicated that RXLD can induce apoptosis, block the cell cycle in the G2/M and S phases, inhibit cell migration via the Wnt/β-catenin pathway, and inhibited p62/Nrf2 pathway. Conclusions: We speculate that the RAS/MAPK pathway might be an upstream pathway through which the RXLD exerts its anti-GBM effects and might be able to regulate further the Wnt/β-catenin, the oxidative stress, and the ferroptosis pathways.